Analysis of the Quality of Aurelia’s Ready-To-Wear Embroidered Set Using Embroidery Techniques Based-on Expert Evaluations - Ayu Yuli Asari; Irmayanti Irmayanti; Shyeika Fatimah Az Zahra; Nisa' Rohmatul Ulya; Nalline Noviandra Eka Fachruzya; Rahmadona Intan Muthia; Nissa Khoirina (Universitas Negeri Semarang, 2026)
This study aims to analyze the quality of the Aurelia Embroidered Set apparel product, which is based on embroidery techniques, using the expert judgment method. The background of this study is rooted in the growing demand for ready-to-wear products that not only possess aesthetic value but also measurable technical and functional quality. The research method used is descriptive quantitative with a product evaluation design. The research subjects consisted of five apparel experts selected using purposive sampling, with an assessment instrument in the form of a Guttman scale covering six indicators: design, sizing, aesthetics, sewing technique, garment performance, and product uniqueness. Data were analyzed using descriptive statistics to determine the percentage of suitability. The results showed that all indicators fell into the “highly suitable” category, with an average percentage of 91.00%. The sewing technique aspect received the highest score, while the sizing aspect received the lowest score but still fell within the “highly suitable” category. The conclusion of this study indicates that the Aurelia Embroidered Set product has good quality in terms of design, production techniques, aesthetics, and comfort, making it suitable for development as an innovative ready-to-wear product in the fashion industry.